Organoleptic Quality Evaluation of Peranakan Etawa Goat Milk Yoghurt (Capra Aegagrus Hircus) with the Addition of Mango Golek (Mangifera indica) - Dwi Syafitri; K M Berutu; J M Sihombing (Talenta Publisher, 2024)
Yoghurt is a drink made from raw milk which has been fermented using a starter which has a slightly thick texture with a slightly sour taste. The purpose of this study was to determine the effect of golek mango juice on the color of yogurt, the texture of yogurt, the taste of yogurt and the aroma of yogurt in the Etawa crossbreed goat's milk by conducting an assessment in organoleptic testing of panelists. This research was conducted at the Laboratory of the Faculty of Agriculture and Animal Husbandry, University of Tjut Nyak Dhien Medan from May to June 2023. The study was conducted using the Kruskall Wallis method with 4 treatments, namely P0 (without golek mango juice), P1 (150 ml/4 g of golek mango juice), P2 (200 ml/6 g of golek mango juice), and P3 ( 250 ml/8 g of golek mango juice) with organoleptic tests consisting of color, texture, taste and aroma. The results showed that the addition of mango juice did not significantly affect the color, texture, taste and aroma of yogurt, however 8 g of mango juice in yoghurt showed the best preference. In conclusion addition of 8 g of golek mango juice is preferred by panelists